Developing the Thought on Students Migration (Which Here Termed As Brain Drain) From Rural Parts of West Bengal and Its Lasting Impact on Society As Well As On the State for Gainful Research: An Empirical Study (International Journal of Innovative Research in Engineering & Management, 2023)
In general parlance, the present study is an  attempt to understand the root causes behind student  migration from rural parts of West Bengal and its overall  impacts on society as well as on the state. The number of  students migrate from rural parts of Bengal is increasing  tremendously. The aim and objective and ultimate  preferences of studying outside the state, is that, students  always prefer to get the option in which they are interested  in and in which they want their specialization, which they  might not be getting in their native colleges and  Universities. The degree which they obtain from that  universities or colleges from that states is considered to be  worth when it comes to searching a good job in any place.  The other benefit of obtaining the degree is most of the  universities or colleges allow the students to go abroad for  completing their final semester. A chance to get educated at  any foreign land might be a distant dream for any middle  class students. Moreover, apart from these factors there are  some key factors like quality education, potential  placement, a good standard of living, and especially a very  poor job opportunities and lower pay scales in the domestic  areas are among the most important reasons for thinking of  migration. There is no doubt that the overall economic  development of the rural parts of Bengal largely depends on  the people, especially on the young generations to a great  extent. If the generation leaves or migrate to other states for  searching of a better future, It should be considered as brain  drain of intellectual resource. Therefore the study initially indicated that constant and  comprehensive monitoring of the trend, and if possible a  regular evaluation process has to be implemented in the  educational institutions to observe the parameter of the  trend. The trend cannot be eradicated permanently , until  and unless State Government, Panchayet, Bank assistance  (Easiest way to get Student’s loan for higher studies),and  above all a State-Central placement cell run and governed  by affiliated Universities are not established immediately.
Keywords: Migration; rural; education; development; urban